Rorschach Assessment of Adolescents Theory, Research, and Practice - Tibon-Czopp, Shira; Weiner, Irving B. (Advancing Responsible Adolescent Development,, 2016)
This book on Rorschach assessment addresses both the complexities of adolescent development and the intricacies of differentiating between normal and abnormal behavioral manifestations. It presents the theory, research, and basic practices of Rorschach assessment and examines the developmental considerations for its use with adolescents, both as a stand-alone instrument and in conjunction with self-report measures. The book's collection of detailed case studies shows the Rorschach method in use with adolescents from different countries across the age group and reflects diverse symptoms. In addition, the new Rorschach Psychoanalytic Science and Practice (RPSP) model endorses the relevance of the method to contemporary practice. Featured coverage includes: Developmental considerations in Rorschach assessment. Diagnostic, forensic, and therapeutic applications of Rorschach assessment with adolescents. An integrative perspective on the Rorschach task and its implications for understanding personality functioning from different psychodynamic perspectives. Psychometric properties of the Rorschach. New normative international data for adolescents. Rorschach Assessment of Adolescents is a must-have resource for researchers, professionals, and graduate students in child clinical and school psychology; forensic medicine; assessment, testing, and evaluation; developmental psychology; and educational psychology. ___________________________________________________ "The clear, elegant conceptualization of complex clinical constructs and fascinating clinical case examples guarantee that this volume will set the standard for psychological assessment of adolescents for many years to come." Ronald J. Ganellen President, Society for Personality Assessment Associate Professor, Northwestern Feinberg School of Medicine "Based on decades of rigorous research, the authors' Rorschach Psychoanalytic Science and Practice model blends empirical rigor with clinical wisdom to capture the uniqueness of adolescents' subjective experience." Robert F. Bornstein President-Elect, Society for Personality Assessment Professor of Psychology, Adelphi University "With an excellent blend of theory and research findings, this book brings Rorschach assessment of adolescents into the contemporary mental health assessment context." Radhika Krishnamurthy Past President, Society for Personality Assessment Clinical Psychology Professor, Florida Institute of Technology .